Książka XV-wieczna w obecnym zasobie Biblioteki WSD w Płocku - Graczyk, Waldemar (Saeculum Christianum. Pismo Historyczne, 2016)
The kept collection of incunabula is not uniform in terms of their origins. Although this is a small collection, in many ways it is interesting concerning both authors, areas of their knowledge, notes of origin or their binding. The library has in total twelve bibliographical positions in ten volumes. They are the work of workshops located in four urban centres: Venice, Cologne, Strasbourg and Augsburg. All of the collection of books are concentrated around four major groups: Scripture, Theology, law and philosophy. The authors of those works were the most prominent representatives of medieval science. Part of the incunabula’s cover are from the period of the book’s print (turn of fifteenth and sixteenth century), part of them are from the later period.